Atomic force microscopy evidence of citrate displacement by 4-mercaptopyridine on gold in aqueous solution - Zhang, Hua (2012)
The displacement adsorption process of 4-mercaptopyridine (4-MP) on trisodium citrate preadsorbed gold surface in aqueous solution was studied using atomic force microscopy (AFM). The measurement was done by monitoring the interaction force between a gold-coated AFM tip and a gold substrate, both presaturated by trisodium citrate. The addition of 4-MP was found to result in a remarkable change of tip−substrate adhesion force, which showed a gradual increase and finally reached a maximum. Using the chemical force titration technique, we estimated the surface pK1/2 of thus-formed 4-MP displacement film and compared with pure 4-MP self-assembled monolayer (SAM) formed on gold in ethanol solution. Our results indicate that the 4-MP molecules are more strongly adsorbed on gold than citrate anions, mostly via Au−S bonding, forming a less dense and mixed displacement film. The displacement adsorption kinetics seems very fast and it takes only ca. 2 min to establish more than 50% surface coverage of 4-MP molecules.